The persistence of active fund management performance - D. R. Wessels; J. D. Krige (South African Journal of Business Management, 2005)
This study focuses on the performance persistence of equity funds in the South African Unit Trust Industry against its appropriate index benchmark (ALSI) over the period 1988 to 2003. A few funds exhibited extraordinary persistence - either in out-performing or under-performing. In general it was found that over the short term (month-to-month and quarter-to-quarter basis) there was a tendency that the current performance of a fund would be repeated, with a greater tendency among the top performing funds to remain a top performer.However, when the persistence of fund performance was measured on a year-to-year basis, less consistency among funds was identified. The decile ranking movement of a fund - upwards, downwards or sideways - became more random in nature. When the forward-looking period was extended to three years, however, the chances that the fund would have stayed in the same decile became very slim.Herein lies the danger of placing your trust with one active manager only; over the long run the performance ranking of managers can assume a random nature if manager skill is not persistent.
Keywords: 650